Purification of Recombinant Proteins from Cultured Mammalian Cells by HaloTag Technology. Issue 1 (1st April 2015) - Ohana, Rachel Friedman; Hurst, Robin
Abstract: Cultured mammalian cells provide an environment ideal for producing functional recombinant mammalian proteins. However, low expression levels of recombinant proteins present a challenge for their detection and purification. This unit will focus on HaloTag, a protein fusion tag designed to bind selectively and covalently to a chloroalkane ligand that may be attached to a variety of functional groups, allowing both protein detection and immobilization. Detection of HaloTag‐fusion protein is achieved through binding to a fluorescent chloroalkane ligand, enabling rapid optimization of expression levels. HaloTag‐based purification uses covalent capture of the HaloTag fusion onto HaloLink resin coupled with proteolytic cleavage to release the protein of interest from the resin. Covalent binding provides efficient protein capture regardless of expression level and eliminates protein loss during washes of the resin and as a result, offers significant improvements in protein recovery and purity over traditional non‐covalent approaches. © 2015 by John Wiley & Sons, Inc.